2012
DOI: 10.2174/1874210601206010220
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Low Intensity Pulsed Ultrasound for Dental Purposes

Abstract: Over the past few years, tissue engineering applied to the dental field has achieved relevant results. Tissue engineering can be described by actions taken to improve biological functions. Several methods have been described to enhance cellular performance and low intensity pulsed ultrasound (LIPUS) has shown to play an important role in cell metabolism. The present article provides an overview about the current status of LIPUS as a tissue engineering tool to be used to enhance tooth and periodontal regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In addition, this treatment has been shown to stimulate periodontal wound healing via enhancement of new bone and cementum formation [20]. Furthermore, several in vitro studies have confirmed the upregulation of a variety of genes related to mineral metabolism [16], cementoblastic differentiation [21], and fibroblast differentiation [22] by LIPUS. Our recent studies demonstrated the beneficial effects of LIPUS in repairing the alveolar bone defect [23] and periodontal fenestration defect [24], and promoting proliferation of hPDLCs in vitro [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this treatment has been shown to stimulate periodontal wound healing via enhancement of new bone and cementum formation [20]. Furthermore, several in vitro studies have confirmed the upregulation of a variety of genes related to mineral metabolism [16], cementoblastic differentiation [21], and fibroblast differentiation [22] by LIPUS. Our recent studies demonstrated the beneficial effects of LIPUS in repairing the alveolar bone defect [23] and periodontal fenestration defect [24], and promoting proliferation of hPDLCs in vitro [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, complete regeneration is hardly achieved. Low‐intensity pulsed ultrasound (LIPUS) has gradually become an innovative and noninvasive method applied in stem cell regeneration and has recently been applied for dental purposes . Studies suggested that LIPUS could enhance cell proliferation activity and promote cell osteogenic differentiation, among other effects .…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that LIPUS could enhance cell proliferation activity and promote cell osteogenic differentiation, among other effects . In the periodontal field, studies have noted that LIPUS stimulation upregulates osteogenic differentiation‐related genes, dentin differentiation genes, and fiber differentiation genes . Additionally, LIPUS accelerates new bone formation and dentine repair .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations